1970
DOI: 10.3126/jnps.v31i3.5361
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhi Infections and Effect of Fluroquinolones and Third Generation Cephalosporins in Clinical Outcome

Abstract: Background: Enteric fever is a common public health problem in Nepal. The emerging fluoroquinolone resistance to Salmonella typhi is a major concern in every hospital and is a public health problem these days. Continuous antibiotic susceptibility patterns surveillance and standard treatment policies need to be established to control MDR typhoid. Objective: To detect the increasing pattern of fluoroquinolone resistant Salmonella typhi and to correlate its clinical response to third generation cephalosporins. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
4
4
2
Order By: Relevance
“…The most commonly aff ected age group (6-10 year) reported in this series is similar to the fi ndings observed by Sharma AK 22 and Singh et al 25 . This age group is more vulnerable to exposure to contaminated foods and water and has not still developed the immunity against the disease.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The most commonly aff ected age group (6-10 year) reported in this series is similar to the fi ndings observed by Sharma AK 22 and Singh et al 25 . This age group is more vulnerable to exposure to contaminated foods and water and has not still developed the immunity against the disease.…”
Section: Discussionsupporting
confidence: 81%
“…This type of seasonal distribution of enteric fever is the typical description of occurrence of enteric fever as mentioned in the textbooks. Similar observations were seen in other series as well 22,23,24,25 . The seasonal variation of occurrence of enteric fever is considered due to more chances of contamination of foods and water by faeces of infected persons and healthy carriers in the rainy season.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A study done in Birendra hospital Kathmandu reported that Ofloxacin was most sensitive antibiotic in 95.23 % cases followed by third generation cephalosporins (Ceftriaxone and Cefixime) in 90.47 % cases. Researchers concluded that third generation cephalosporins may be the alternative for the treatment of fluoroquinolone resistant typhoid fever 23 . On the reference to these facts we reviewed current treatment pattern of typhoid fever in Nepal.…”
Section: Resultsmentioning
confidence: 99%